The Digital Revolution in Exploring the Impact of Fintech on Islamic Financial Services - Haris, Chadijah; Manangin, Sakila (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2024)
The implementation of financial technology (fintech) at Bank Syariah Indonesia KCP Bitung has significantly impacted financial inclusion, particularly through the BSI Mobile application. This study examines how fintech has enhanced accessibility to Islamic financial services, especially for individuals previously underserved by conventional banking systems. The findings reveal that fintech has not only expedited financial transactions but also provided customers with easier access to a variety of financial features, thereby improving their financial management capabilities. Interviews with bank staff and customers indicated that fintech solutions like BSI Mobile offer convenience, efficiency, and flexibility in the digital era. However, the research also identifies challenges, including the need for adequate infrastructure, intensive education and socialization regarding fintech usage, and potential security risks in digital transactions. To address these challenges, it is crucial for Islamic banks to foster innovation and collaboration with fintech providers to offer more inclusive and affordable solutions, thus broadening the reach of Islamic financial services. The emphasis on ongoing innovation and collaboration is key to integrating technology with Islamic finance, creating a more inclusive, transparent, and sustainable financial ecosystem that supports equitable economic growth within society.